The Effectiveness Of Using The Herringbone Technique On Students' Reading Comprehension Skill In Recount Text In The Eighth Grade Of Smp Gajah Mada Medan - Turnip, Putri Kumala Br; Lestari, Febrika Dwi; Sinaga, Nenni Triana (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
The objective of this research was to find out the effectiveness of using the herringbone technique on students’ reading comprehension skill in recount text. This research was conducted at SMP Gajah Mada. The population of this research was the 8 grade students of the academic year 2023/2024. One class consisted of 34 students. The sample consisted of 34 students and was taken by using quasi-experimental. The sample is divided into 2 groups, the experimental group which consisted of 17 students, and the control group consisted of 17 students. The instrument for collecting data was a reading test. Each group was given a pre-test and post-test. The result of this research showed that the mean score of the experimental group is higher (93,23) than the control group (70,58). Based on the calculation above the alternative hypothesis (Ha) is accepted. It is found from the computation of the t- test that the t-observed is higher than the t-table (7,2> 1,694) at the level significance of one tail test (p=0.05) with a degree of freedom (df-32). The final hypothesis showed that HO was rejected and Ha was accepted. This means that there was a significant effectiveness of using the herringbone technique on students’ reading comprehension skill.